2001
DOI: 10.1021/om010373o
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Bis(pentafluorophenyl)borane with Cp2Ta(CH2)CH3:  Generation and Trapping of Tantalocene Borataalkene Complexes

Abstract: plus 1 equiv of H 3 CB(C 6 F 5 ) 2 . The pathway to 1 involves stepwise attack of borane first at the methylene group, followed by attack at the methyl group, which undergoes alkyl/hydride exchange with the second equivalent of HB(C 6 F 5 ) 2 . The product of HB(C 6 F 5 ) 2 addition to the methylene ligand, methyl hydride complex Cp 2 -Ta(CH 2 B(C 6 F 5 ) 2 )(µ-H)(CH 3 ), 2, can be intercepted by carrying out the reaction in hexane at low temperature, a medium in which it is nearly totally insoluble. This comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 80 publications
1
36
0
Order By: Relevance
“…A number of examples of complexes containing metalborane coordination have now been reported [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Metal-borane complexes have been synthesised from nearly all of the late transition metals (groups [8][9][10][11].…”
Section: Brief Survey Of Metallaboratranes Their Geometries and Strumentioning
confidence: 99%
See 1 more Smart Citation
“…A number of examples of complexes containing metalborane coordination have now been reported [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Metal-borane complexes have been synthesised from nearly all of the late transition metals (groups [8][9][10][11].…”
Section: Brief Survey Of Metallaboratranes Their Geometries and Strumentioning
confidence: 99%
“…Despite the classification of this mode of coordination for some time, they had received little attention. There were few examples of Z-type ligands claimed prior to the discovery of the metallaboratrane compounds and many of these examples were also later disproved [32][33][34][35][36][37][38][39][40][41][42]. This can be ascribed to the instability of the resulting compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[1,[4][5][6] While the chemistry of borataalkenes has not been widely investigated, studies have shown that they can act as nucleophilic reagents [4][5][6] or as ligands in transition-metal complexes. [7][8][9] Electrogenerated diborataalkenes, such as [p-(Mes 2 B)C 6 H 4 (BMes 2 )] 2À , have also been detected using spectroelectrochemistry. [10][11][12] Interestingly, however, the structural changes accompanying the stepwise population/depopulation of a boron-carbon p bond have not been studied experimentally.…”
mentioning
confidence: 99%
“…As expected, the dimesitylboryl moiety is efficiently π-conjugated with the p-phenylene backbone as evidenced by the relatively small dihedral angle of 23.6 • formed between the planes defined by C(20)-B(1)-C(29) and C(3)-C(4)-C(5). On the other hand, the dihedral angle of 66.0 • formed by the C(8)-C(7)-C (19) and C(2)-C(1)-C(6) planes indicates that the xanthenium unit is not efficiently conjugated with the rest of the molecule.…”
Section: Synthesis and Structurementioning
confidence: 99%
“…Borataalkenes, which have been known for several decades, can be regarded as borylated carbanions stabilized by π-conjugation of the carbanion lone pair with the empty p-orbital of the boron atom [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Recently we have demonstrated that borataalkene derivatives can also be obtained by reduction of borylated carbocationic derivatives such as [C] + [20,21].…”
Section: Introductionmentioning
confidence: 99%